Efecto hipolipemiante de Hibiscus sabdariffa en pacientes con dislipidemia - Hernández Martínez, Alejandro; Lobo Moreno, Jorge Arturo; Noveron Miranda, Sonia (Universidad Autónoma Metropolitana, 2003)
High circulation levels of total cholesterol, as well as low density lipoproteins and triglycerides, are related with many chronic degenerative diseases, such as hypertension and cardiopathies. The anti-hyperlipidemic agents currently in use, show us great effectiveness in his task, but multiple side effects and their cost limit their use. Hibiscus sabdariffa (jamaica flower) show us an important reducing effect in the circulating levels of lipids in blood when used in the form of cold tea. The purpose of this work is to examine the effect of a dry extract of hibiscus sabdariffa on the blood levels of lipids. METHOD. We carried out a comparative experimental, open, prospective and longitudinal study with 20 patients with different levels of hyperlipidemia. They were formed in four groups and four treatments were administered: hibiscus sabdariffa cold tea, plain water additional to the normal intake, encapsulated dry extract and placebo. The blood levels of cholesterol, low density lipoproteins, high density lipoproteins and triglycerides were taken at the beginning of the study and at 30 and 60 days of treatment to know the effect of the therapeutic forms. RESULTS. Levels of total cholesterol, LDL and triglycerides diminished between 19% and 26% at 60 days (p < 0.05) before the patients took extract of hibiscus sabdariffa flower, whether it was taken in the form cold tea or encapsulated dry extract. The level of high density lipoproteins rose in a similar way. Patients, whom received additional drinking water or placebo, didn't experience any changes in the final lipid profile. KEY WORDS: Hibiscus sabdariffa, lipid profile, antihyperlipidemic agents, total cholesterol, low density lipoprotein, high density lipoprotein, triglycerides.; ANTECEDENTES. Los niveles séricos elevados de colesterol total, de lipoproteínas de baja densidad y de triglicéridos, se relacionan frecuentemente con diversas enfermedades crónico degenerativas como las cardiopatías y la hipertensión arterial. Los medicamentos hipolipemiantes existentes en el mercado, demuestran una eficacia adecuada en el control de las dislipidemias, sin embargo, los efectos secundarios y su elevado costo limitan su uso. Hibiscus sabdariffa (flor de jamaica) muestra un importante efecto para reducir los niveles de lípidos en sangre, administrada en forma de tizana fría. El objetivo de éste trabajo es examinar el efecto de un extracto seco encapsulado de hibiscus sabdariffa sobre los niveles séricos elevados de lípidos. METODO. Se realizó un estudio comparativo, abierto, experimental, prospectivo y longitudinal con 20 pacientes con diversos grados de dislipidemia. Se formaron cuatro grupos y se administraron cuatro tratamientos: tizana fría, un litro de agua adicional, extracto seco encapsulado y placebo. Se determinaron los niveles séricos de colesterol total, LDL, HDL y triglicéridos al inicio del estudio, a los 30 y a los 60 días para conocer el efecto de los cuatro tratamientos. RESULTADOS. Los niveles de colesterol total, LDL y triglicéridos disminuyeron entre un 19% y un 26% a los 60 días (p< 0.05) en los pacientes que tomaron el extracto de flor de jamaica, tanto en forma de tizana como en la de polvo encapsulado. El nivel de HDL se elevó en un porcentaje similar. Los pacientes a los que se les administró agua potable adicional o placebo, no experimentaron cambio en el perfil lípido final. PALABRAS CLAVE: Hibiscus sabdariffa, perfil lípido, dislipidemia, hipolipemiantes, colesterol total, LDL, HDL, triglicéridos.